Strategi Penanganan Non-Performance Loan pada PT PNM di Masa Pandemi - Hanhan Priatna Priatna; Eduardus Suharto (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2023)
The study of non-performing loans (NPL) to non-bank financial institutions (NBFIs) is very crucial for various stakeholders. The purpose of this study was to determine the effect of restructuring, Write-off, Outstanding, and Portfolio at Risk (PAR) during the Covid-19 Pandemic on NPL at Permodalan Nasional Madani (PNM). The research analyzed data from January 2020 to March 2022 at three branches of PT PNM, using 81 observational data points. The study employed descriptive analysis to describe the collected data and utilized the multiple linear regression approach, with EViews application, to determine the impact of multiple independent variables on the dependent variable. Restructuring negatively impacts NPL but has positive implications. The implementation of restructuring at PT PNM during the Covid-19 Pandemic led to a decrease in NPL. A decrease in outstanding loans also negatively affects NPL, reducing the risk of NPL at PT PNM during the pandemic. Write-offs have a negative effect on NPL but beneficial implications, as they help control NPL at PT PNM during the Covid-19 Pandemic. Portfolio at Risk (PAR) has a positive effect on NPL, indicating an undesirable condition. Ideally, PAR should have a negative effect on NPL, but PT PNM still faced challenges in managing NPLs and PAR during the pandemic. The research novelty expected from this study is the finding of consideration of different characteristics, regulatory frameworks, and NPL risk profiles in NBFIs compared to conventional banks.